False belief understanding in deaf children: what are the difficulties? - Meristo, Marek; Surian, Luca; Strid, Karin (Frontiers in Psychology, 2024)
Children with cochlear implants (CIs) demonstrate proficiency in verbal-story elicited-response (VS-ER) false-belief tasks, such as the Sally & Ann task, at a similar age as typically developing hearing children. However, they face challenges in non-verbal spontaneous-response (NV-SR) false-belief tasks, measured via looking times, which hearing infants typically pass by around two years of age. The purpose of the present study was to examine whether these difficulties remain in a non-verbal-story elicited-response (NVS-ER) false-belief task, in which children are offered the opportunity to provide an elicited response to a non-verbal-story task. A total of thirty 4- to 8-year-old children with CI-s and hearing children completed three different kinds of false-belief tasks. The results showed that children with CI-s performed above chance level on the verbal task (i.e., VS-ER task), but not on the two non-verbal tasks, (i.e., NVS-ER and NV-SR tasks). The control group of typically developing hearing children performed above chance on all three kinds of tasks (one-tailed significance level). Our findings highlight the importance of external narrative support for children with CIs in tasks that involve mental perspective-taking, and specifically predicting actions based on false beliefs. Abbreviations: CI – cochlear implant; VS-ER – verbal-story elicited-response; NV-SR – non-verbal spontaneous-response; NVS-ER – non-verbal-story elicited-response